Como “me tornei” educadora popular: trajetórias de alfabetizadoras de pessoas adultas - Santana, Leyla Menezes de (2020)
How “have I become” a popular educator? This is the leading question to this thesis which aimed at understanding the process of becoming a popular educator through the analysis of trajectories narrated by women who worked in a project for Young Adults and Adults Education, led by Pastoral da Criança from 1993 to 2017, in the state of Sergipe, Brazil. It results from a research developed with popular female educators who lived a pedagogy conceived in community frontiers, embraced by diverse knowledge, entangled in singular and subjective narratives. To build the encounter with these six female educators, residing in communities from the municipalities of Lagarto and Ilha das Flores, in the state of Sergipe, was a movement that has delimited this research the most. In this movement, methodologically named inter-encounter, it was important to listen, with sensitivity, to those women who have become educators while living the process, who would share their own experiences through a constant process of making and re-making diverse knowledge, moving beyond what was already known. This paper was supported by methodological assumptions of Hermeneutical Phenomenology as an approach method and the Oral History as a procedural method, apprehending narratives and collecting testimonials resulting from interencounters through three movements: inter-hearing, self-writing, and conversation circle. In order to analyze how they have become educators, different conceptual tools were used, in the field of memory and experience, even stablishing a dialogue with Popular Education theoretical assumptions, intertwined with a Freirean analytical perspective, in consonance with adult literacy. From narrative contextures, four main axes emerged in order to respond to the research problemquestion: provocation-action, teaching mystique, community belonging, and the experiences with Pastoral da Criança. From these axes, it was confirmed that these women have become popular educators by provocation-action which resulted in educating as a mission, pedagogically conducted by the mystique of teaching and learning, circumscribed in community belongings, and crossed by experiences with Pastoral da Criança.